Protective Effects of Otophylloside N on Pentylenetetrazol-Induced Neuronal Injury In vitro and In vivo - Sheng, Feiya; Chen, Mengting; Tan, Yuan; Xiang, Cheng; Zhang, Mi; Li, Baocai; Su, Huanxing; He, Chengwei; Wan, Jianbo; Li, Peng (Frontiers in Pharmacology, 2016)
Approximately 30% of epileptic patients worldwide are medically unable to control their seizures. In addition, repeated epileptic seizures generally lead to neural damage. Pentylenetetrazol (PTZ) is a clinical circulatory and respiratory stimulant that is experimentally used to mimic epileptic convulsion in epilepsy research. Here, we systematically explore the neuroprotective effects of a pure compound isolated from Cynanchum otophyllum Schneid (Qingyangshen), Otophylloside N (OtoN), against PTZ-induced neuronal injury. We used three models: in vitro primary cortical neurons, in vivo mice and in vivo zebrafish. Our results revealed that OtoN treatment may attenuate PTZ-induced morphology changes, cell death, LDH efflux in embryonic neuronal cells of C57BL/6J mice, and convulsive behavior in zebrafish. Additionally, our Western blot and RT-PCR results demonstrated that OtoN may attenuate PTZ-induced apoptosis and neuronal activation in neuronal cells, mice and zebrafish. OtoN may reduce PTZ-induced cleavage of poly ADP-ribose polymerase (PARP) and upregulation of the Bax/Bcl-2 ratio and decrease the expression level of c-Fos. This study is the first investigation of the neuroprotective effects of OtoN, which might be developed as a novel antiepileptic drug.